Deteksi Lokasi Perubahan Penutup Lahan Untuk Meminimalkan Risiko Keamanan Wilayah - Rahmadya Trias Handayanto; Haryono; Ramdhani Setiawan (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2024)
Changes in land use and cover of an area significantly affect the quality of the area, especially from a socio-economic perspective. If city and regional governments are unable to anticipate these changes, it can greatly impact the security of the area, such as a lack of availability of public facilities, increased crime, and other social aspects. Research on changes in land use and cover has mostly focused on agriculture and rarely addresses regional security. Therefore, this study focuses on changes in land use, particularly in the type of urban residential land use in Bekasi city. The data used are Landsat satellite images from two different years for the Bekasi city area, utilizing trend change analysis with the Idrisi Selva application. Initially, a land cover classification process was carried out using the Iterative Self-Organizing Clustering (ISOCLUST) method, followed by reclassification with the same application into five classes: agriculture, vacant land, buildings, vegetation, and water bodies. The results show the direction of land change development where residential areas increase in the direction according to the degree of trend change, namely to the lower middle for the third degree and to the northwest and lower middle for the fifth degree. The research results can be used by regional planners in creating Spatial and Regional Plans (RTRW) as well as Detailed Spatial Plans (RDTR).